SURG-11. Surgery for control of brain metastases after prior checkpoint inhibitor immunotherapy: a single-center series. (9th August 2021) - Morshed, Ramin; Chung, Jason; Sudhakar, Vivek; Cummins, Daniel; Young, Jacob; Hervey-Jumper, Shawn; Theodosopoulos, Philip; Aghi, Manish
Abstract: Background: Despite the promising results for treating metastatic cancer with checkpoint inhibitor immunotherapies, there are limited data on surgical outcomes for brain metastases (BMs) that have progressed after prior checkpoint inhibitor treatment. The objective of this study was to identify factors associated with local progression, leptomeningeal disease, and survival for patients undergoing surgical resection of a BM in patients previously treated with checkpoint inhibitor immunotherapy. Methods: A retrospective, single-center cohort study was conducted with inclusion of adult patients undergoing surgical resection of a BM in the setting of progression after prior checkpoint inhibitor treatment. Univariate and multivariate analyses were performed to identify factors associated with outcomes of interest. Results: Over an 8-year period, 26 patients who underwent resection of 30 BMs met inclusion criteria. Median patient age at surgery was 63.9 years, and median clinical follow-up was 6.9 months (range 0.1 – 52.9). Extracranial disease was present at the time of surgery in 73.3% of cases. There were 6 postoperative complication events (20% of cases) by 30-days. By last follow-up, 65.4% of the cohort had died with a median censored survival of 7.6 months from surgery. Eight patients (30.8%) died within 3 months of surgery. On multivariate analysis, postoperative complications were associated with worse survival (HR 5.33, 95%CI 1.15–24.77, p=0.03). Four BMs had local progression (13.3%), and 60% of procedures were associated with distant progression within a median time of 3.6 months. Leptomeningeal disease developed in 32% of cases. On multivariate analysis, increased time from BM diagnosis to surgery was associated with a greater risk of leptomeningeal disease (OR 1.2, 95%CI 1.00–1.43, p=0.021). Conclusion: Patients who require BM resection after prior checkpoint inhibitor treatment have an overall poor prognosis. Although local control rates are acceptable, these patients are at high risk for developing leptomeningeal disease postoperatively.